Evaluation the Effects of Fe3O4 Nanoparticles on Biofilm Genes Expression Patterns in Acinetobacter baumannii using Quantitative Real-Time Polymerase Chain Reaction Assay - Haider Turky Al-Mousawi (Journal of Global Pharma Technology, 2016)
We selected Acinetobacter baumannii isolate from different clinical sources (wounds, burns, urine, sputum, blood and throat) that ability to produce strong biofilm formation, Nanotechnology technique is used in this study, Synthesis magnetic iron oxide nanoparticles Fe3O4 NPs using co-precipitation method and detailed physical-chemical characterization, the results show is very fine crystalline sizes reach to 11±1 nm by XRD ,with mostly spherical in shape and average nanoparticles size at (40- 47) nm by SEM and AFM respectively. The minimum inhibitory concentration (MIC) and sub-MIC test of Fe3O4 NPs at concentrations (15.75 to 2000) μg/ml toward A.baumannii isolates had been determined using Tube broth method. The best sub-MIC concentration of Fe3O4 NPs was 125μg/ml with a significant difference at p˃0.05 enhanced bacterial adhesion inhibitory on polystyrene surface of microtiter plates and consequently caused biofilms. The results of investigate gene expression of biofilm formation CsuE gene with reference 16SrRNA gene by RT-qPCR technique before and after treatment with Fe3O4 NPs show a significant difference at p˃0.05 in Cycle threshold (Ct) values for gene expression for CsuE gene of the isolates. Therefore these treated enhance a significant difference lowest of expression gene fold value for CsuE gene and up-regulated at physiological biofilm, while 16SrRNA gene confirmed as well suitable housekeeping gene because do not appear any variations of expression before and after Fe3O4 NPs treated.Keywords: Acinetobacter baumannii, Fe3O4 NPs, Biofilm Formation, Biofilm gene and gene expression.